GOCE’s view below the ice of Antarctica: Satellite gravimetry confirms improvements in Bedmap2 bedrock knowledge - Hirt, Christian (American Geophysical Union, 2014)
Accurate knowledge of Antarctica's topography, bedrock, and ice sheet thickness is pivotal for climate change and geoscience research. Building on recent significant progress made in satellite gravity mapping with European Space Agency's Gravity field and Ocean Circulation Explorer (GOCE) mission, we here reverse the widely used approach of validating satellite gravity with topography and instead utilize the new GOCE gravity maps for novel evaluation of Bedmap1/2. Space-collected GOCE gravity reveals clear improvements in the Bedmap2 ice and bedrock data over Bedmap1 via forward modeled topographic mass and gravity effects at spatial scales of 400 to 80 km. Our study demonstrates GOCE's sensitivity for the subsurface mass distribution in the lithosphere and delivers independent evidence for Bedmap2's improved quality, reflecting new radar-derived ice thickness data. GOCE and Bedmap2 are combined to produce improved Bouguer gravity maps over Antarctica. We recommend incorporation of Bedmap2 in future high-resolution global topography and geopotential models and its use for detailed geoid modeling over Antarctica.